Zadania policji w zakresie przeciwdziałania terroryzmowi - Otczyk, Robert (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article discusses the remit of the police with regard to counteracting terrorism. There are four directions areas in which police forces operate to counteract terrorism. These are: first — prevention, education and cooperation; second — recognition and information processing; third — police negotiations; fourth — physical fight against terrorism. With regard to that last issue it must be noted that tasks associated with physical elimination of terrorism fall within the remit of special anti-terrorist units of the police.
Keywords: policja; terroryzm; bezpieczeństwo narodowe; antyterroryzm; zagrożenia bezpieczeństwa; jednostki specjalne policji